2018
DOI: 10.1007/s00431-018-3182-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of intravenous immunoglobulin-resistant Kawasaki disease in children: a meta-analysis of 4442 cases

Abstract: The purpose of this study was to identify the clinical features and laboratory factors that are predictive of intravenous immunoglobulin (IVIG)-resistant Kawasaki disease. Multiple databases were searched for relevant studies on IVIG-resistant Kawasaki disease published from January 2002 to April 2017. Eligible studies were retrieved by manual review of the references. Stata 12 was used for the meta-analysis. Weighted mean differences and odds ratios with 95% confidence intervals were calculated for several in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 42 publications
3
44
0
1
Order By: Relevance
“…[5,6] Based on a meta-analysis, when patients who were IVIG-resistant and -responsive were compared, the hemoglobin level, leukocyte and platelet counts, and ESR were statistically signi cant. [30] In our study the increased risk of IVIG resistance was shown to be statistically signi cant, especially in the group < 5 years of age. When the laboratory ndings of our IVIG-resistant patients were examined, a signi cant increase existed in the leukocyte count (marked neutrophil increase), platelet count, and CRP, ALT, troponin T and NT-proBNP levels, while the hematocrit and sodium levels were signi cantly decreased.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…[5,6] Based on a meta-analysis, when patients who were IVIG-resistant and -responsive were compared, the hemoglobin level, leukocyte and platelet counts, and ESR were statistically signi cant. [30] In our study the increased risk of IVIG resistance was shown to be statistically signi cant, especially in the group < 5 years of age. When the laboratory ndings of our IVIG-resistant patients were examined, a signi cant increase existed in the leukocyte count (marked neutrophil increase), platelet count, and CRP, ALT, troponin T and NT-proBNP levels, while the hematocrit and sodium levels were signi cantly decreased.…”
Section: Discussionsupporting
confidence: 51%
“…Indeed, there are several studies with similar results. [30][31][32][33] 33. Mann-Whitney U test was used for non-parametric testing c "Average" and "standard deviation" values in parentheses were speci ed for normally distributed data d "Median" and "lowest -highest values" in parentheses were speci ed for non-normally distributed data ALT: alanine transaminase; AST: aspartate aminotransferase; K: potassium; Na: sodium; NEU (%): neutrophil/leukocyte ratio; PLT: platelet count; NT-proBNP: N-terminal-pro-brain natriuretic peptide; WBC: White blood cell Mann-Whitney U test was used for non-parametric testing c "Average" and "standard deviation" values in parentheses were speci ed for normally distributed data d "Median" and "lowest -highest values" in parentheses were speci ed for non-normally distributed data ALT: alanine transaminase; AST: aspartate aminotransferase; K: potassium; Na: sodium; NEU (%): neutrophil/leukocyte ratio; PLT: platelet count; NT-proBNP: N-terminal-pro-brain natriuretic peptide; WBC: White blood cell…”
Section: Discussionmentioning
confidence: 99%
“…Between 10% and 20% of patients with KD have persistent or recurrent fever after primary therapy with IVIG plus ASA ( 2 , 22 , 23 ). Because the probability of coronary artery damage associated with IVIG-resistant KD is higher than IVIG-sensitive KD, the probability of damage to the coronary arteries would decrease, as well as the cost and hospitalization time, if patients with IVIG-resistant KD can be detected and appropriately treated before additional IVIG treatment ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the correlation between FC and IVIG unresponsiveness indicates that an elevation of FC levels in children with KD could be a re ection of pathogenesis that could lead to IVIG unresponsiveness. IVIG unresponsiveness in children with KD has been presumed to correlate with the severity of in ammation [23,24].…”
Section: Discussionmentioning
confidence: 99%